Incision‐free, coronally advanced flap with subepithelial connective tissue graft placed by the molar or canine access (MOCA) technique: 13 case series. Issue 1 (4th May 2022) - Kashani, Hooshang; Vora, Manali V.; Kuraji, Ryutaro; Fathi‐Kelly, Hoorshad; Nguyen, Trung; Tamraz, Beniel; Tran, Christine; Kapila, Yvonne L.
Abstract: Introduction: Root coverage procedures are not always predictable, and outcomes depend on several factors. This technique provides a predictable alternative to managing facial gingival recessions. Case Series: A new grafting technique is introduced that requires no incisions at the recipient site, thereby preserving the integrity of the local blood supply to optimize the healing process. The graft is placed through the gingival sulcus via a molar or canine access (MOCA) approach, and there is minimal tension on the coronally advanced flap through use of suspension sutures. Thirteen non‐smoking patients, between the ages of 27 and 57, with Cairo RT1 facial recession were studied, with a follow‐up period of 1–60 weeks. This paper explains the step‐by‐step technique and highlights 13 cases. Conclusion: Complete root coverage was achieved in all 13 cases, although one case showed initial altered healing. While MOCA is technique sensitive, it provides optimal root coverage results. With no incisions at the recipient site, there is no uneven texture or scar formation, and healing proceeds with minimal interruption. Why is this case series new information? MOCA is a unique approach to introduce grafts into non‐incised sites of recession that can be one, two, or three teeth away at molars or canines. Non‐incised approach minimizes interruption to blood supply. Coronally advanced flaps are secured in place with composite‐fastened suspension sutures for tension‐free flap closure. What are the keys to successful management of these cases? Good quality and quantity of connective tissue graft Early diagnosis and treatment of recession Expert surgical technique What are the key limitations to the success of these cases? The quality of the donor site is variable among patients. A technique‐sensitive approach Advanced recession might warrant a second surgery.